2007
DOI: 10.1002/pros.20620
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of benign and malignant prostate epithelial Hoechst 33342 side populations

Abstract: Our observations are consistent with the Hoechst 33342 dye efflux assay isolating a stem cell enriched population which can be further sub-fractionated by CD133 selection. Moreover, the loss of the CDK inhibitor in malignancy is consistent with the hypothesis that neoplastic change originates in the stem cell compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 67 publications
2
68
1
Order By: Relevance
“…The SP fraction has been identified in numerous cancers, including neuroblastoma, breast cancer, prostate cancer and gastrointestinal carcinoma, and their chemoresistance is due to the ability of multidrug-resistant stem/progenitor cells to efflux anticancer drugs such as mitoxanthrone, gemcitabine, doxorubicin or 5-fluorouracil [44, [101][102][103]. Moreover, in the presence of mitoxanthrone, the SP cell frequency in neuroblastoma was increased [102].…”
Section: Reviewmentioning
confidence: 99%
“…The SP fraction has been identified in numerous cancers, including neuroblastoma, breast cancer, prostate cancer and gastrointestinal carcinoma, and their chemoresistance is due to the ability of multidrug-resistant stem/progenitor cells to efflux anticancer drugs such as mitoxanthrone, gemcitabine, doxorubicin or 5-fluorouracil [44, [101][102][103]. Moreover, in the presence of mitoxanthrone, the SP cell frequency in neuroblastoma was increased [102].…”
Section: Reviewmentioning
confidence: 99%
“…ABCG2 was shown to be efficient at Hoechst dye efflux, creating a side population (SP) phenotype that has been used as an alternate approach to identify multipotent stem cells in bone marrow, skeletal muscle, and neural tissue (Bunting 2002) and more recently in the prostate (Bhatt et al 2003). The SP cells of the prostate have slightly higher sphere-forming activity in vitro than the non-SP cells, although only by fourfold (Brown et al 2007). Further characterization showed that only 1% of the basal cells were included in the SP fraction, and they expressed known stem cell genes such as nestin, Bmi-1, hTeRT, and CD133 (Pascal et al 2007).…”
Section: Human Prostate Stem Cellsmentioning
confidence: 99%
“…These include the cells that preferentially express CD44 (13), ␣2␤1 (i.e. ␣2␤1 hi ) (14), or CD133 (15,16) and the side population (17), whose phenotype is mediated by multidrug resistance family proteins, such as MDR-1 and ABCG2 (18). Interestingly, the ABCG2 ϩ cells in the benign prostate constitute Ͻ1% of total basal cell population and share essentially the same transcriptome as the side population cells (19).…”
mentioning
confidence: 99%